2022
DOI: 10.3389/fnut.2022.857823
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Dietary Vitamin C and E Intake With Depression. A Meta-Analysis of Observational Studies

Abstract: ObjectiveThe associations of dietary vitamin C and E intake with depression remains conflicting. This meta-analysis of observational study was therefore employed to clarify the issue further.MethodsAn extensive literature review (PubMed, Web of Science and Embase) was performed in January 2022 to identify the observational studies on the associations of dietary vitamin C and E intake with depression. The pooled relative risk (RR) of depression for the highest versus lowest dietary vitamin C and E intake catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 59 publications
1
16
2
Order By: Relevance
“…Li et al used NHANES data from 2009 to 2014 to show that copper is inversely related to depressive symptoms, which is consistent with the results of our study ( 39 ). In contrast to our study, a meta-analysis of 25 observational studies showed an inverse association between vitamin E and depressive symptoms ( 40 ). Second, our study showed that, after adjusting for a variety of nutrients, caffeine consumption is positively associated with depressive symptoms.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Li et al used NHANES data from 2009 to 2014 to show that copper is inversely related to depressive symptoms, which is consistent with the results of our study ( 39 ). In contrast to our study, a meta-analysis of 25 observational studies showed an inverse association between vitamin E and depressive symptoms ( 40 ). Second, our study showed that, after adjusting for a variety of nutrients, caffeine consumption is positively associated with depressive symptoms.…”
Section: Discussioncontrasting
confidence: 99%
“…Factor 3, mainly vitamins and dietary fiber, was negatively correlated with depressive symptoms and CRP, with the same results in the entire group, the >50-year-old subgroup, and the male subgroup. A meta-analysis showed that vitamin C intake was inversely associated with depressive symptoms ( 40 ), and that tocopherol treatment prevented TNF-α-induced depressive symptoms in mice ( 42 ). In addition, studies showed that oxidative stress in patients with depressive symptoms increases ( 43 , 44 ), and the intake of vitamin C, vitamin E, and folic acid is related to a reduction in oxidative stress ( 45 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, con icting results were also found in two meta-analyses [20,21]. A meta-analysis involving 25 observational studies demonstrated a negative relationship between vitamin C and depression [20]. Conversely, another meta-analysis showed that vitamin C supplementation was ineffective for reducing depressive symptoms [21].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C is vital for human health as it plays a critical role in human metabolism and is utilized in the treatment of oxidative stress-related diseases [15]. To date, several studies have been conducted to investigate the relationship between vitamin C and depression [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the intake of dietary sugar, fat, and protein in life also contains some additives such as sweeteners, preservatives, and other ingredients, and their relationships with depression are not clear, which should be addressed in follow-up studies. Furthermore, the nutritional elements associated with depression not only include those summarized in the article but also involve vitamins [ 176 , 177 , 178 ], folic acid [ 179 ], N-acetylcysteine [ 180 ], S-adenozylmetionine [ 181 ], dietary fiber [ 182 ], etc., which also need to be considered. This article suggests that to better prevent and treat depression, people should gradually focus on the role of nutrients in depression and their daily diet, such as low-sugar and low-fat diets.…”
Section: Discussionmentioning
confidence: 99%